Synthesis, crystal structure, magnetic and vibrational properties of formamidine-templated Co and Fe formates. (8th January 2015) - Ciupa, Aneta; Mączka, Mirosław; Gągor, Anna; Pikul, Adam; Kucharska, Edyta; Hanuza, Jerzy; Sieradzki, Adam
Abstract : Graphical abstract: We report the synthesis, structure, magnetic and phonon properties of two novel [NH2 –CH–NH2 ][M(HCOO)3 ] formates (M = Co, Fe). These compounds are isostructural and crystallize in the orthorhombic structure, space group Pnna, with ordered FMD + cations located in the cavities of the network. They are weak ferromagnets, with the critical temperatures of 13.0 K (Co) and 17.0 K (Fe). Abstract: Two novel Co and Fe formates, [NH2 –CH–NH2 ][Co(HCOO)3 ] and [NH2 –CH–NH2 ][Fe(HCOO)3 ], containing formamidinium cations [FMD +, NH2 –CH + –NH2 ] have been prepared under solvothermal conditions. Crystal structure determination shows that these compounds are isostructural and crystallize in the orthorhombic structure, space group Pnna . The FMD + cations, located in the cavities of the metal formate framework, form extensive N–H⋯O hydrogen bonding with the framework and they are ordered at room temperature. The divalent cations have octahedral geometry and are bridged by the formate ions in an anti–anti mode of coordination. A magnetic study revealed that these compounds are weak ferromagnets, with the critical temperatures of 13.0 K (Co) and 17.0 K (Fe). Based on IR and Raman data, an assignment of the observed modes has been proposed.